The Absent and Disinterested Other: Henry James’s Experimental First Person Narrative in “The Ghostly Rental” (1876) - Nabae, Hitomi (Litteraria Copernicana, 2017)
The article is an analysis of Henry James’s ghost story titled “The Ghostly Rental.” The author focuses, first of all, on the first-person narrat ion in this story, published in 1876, soon after James left the United States. The author also examines the figure of the narrator’s friend.